2006
DOI: 10.1364/opex.14.000279
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced coupling of terahertz radiation to cylindrical wire waveguides

Abstract: Wire waveguides have recently been shown to be valuable for transporting pulsed terahertz radiation. This technique relies on the use of a scattering mechanism for input coupling. A radially polarized surface wave is excited when a linearly polarized terahertz pulse is focused on the gap between the wire waveguide and another metal structure. We calculate the input coupling efficiency using a simulation based on the Finite Element Method (FEM). Additional FEM results indicate that enhanced coupling efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 0 publications
1
68
0
6
Order By: Relevance
“…Of these modes, only a single, radially polarized mode survives after propagating along the length of the wire for several cm's. While it has been shown that this scattering technique is not the most efficient method of coupling terahertz radiation to a wire waveguide [13], it is a simple and effective method, and is adequate for these measurements. The surface wave propagates towards the end of the wire where it is partially scattered into free space.…”
Section: Methodsmentioning
confidence: 99%
“…Of these modes, only a single, radially polarized mode survives after propagating along the length of the wire for several cm's. While it has been shown that this scattering technique is not the most efficient method of coupling terahertz radiation to a wire waveguide [13], it is a simple and effective method, and is adequate for these measurements. The surface wave propagates towards the end of the wire where it is partially scattered into free space.…”
Section: Methodsmentioning
confidence: 99%
“…The same near-field edge-coupled source can be used as an alternative method (to [12][13][14]) for exciting waveguides without THz optics.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, metallic waveguides such as single wire waveguides [6,7], parallel plate waveguides [8] and two-wire waveguides [9][10][11][12] support the propagation of single cycle THz pulses with low dispersion due to their (almost) non-dispersive transverse electromagnetic mode (TEM). Single wire waveguides carrying radially polarized TEM modes are difficult to excite from commonly available linearly polarized THz sources -such as photoconductive (PC) antennas -due to mode mismatch, and hence it is necessary to make use of a radially polarized THz radiation source [13]. Furthermore, single-wire waveguides are featured by high bending losses, which limit the flexibility of such a solution.…”
Section: Introductionmentioning
confidence: 99%